Happiness Differences by Sex and Age in Peruvian University - Castilla, Humberto (2016)
The study, comparative descriptive, describes the differences of happiness in Peruvian youth and adults based on sex and age using the Lima Happiness Scale (Alarcon, 2006). 402 people, male (50 %) and women (50 %), between 16 and 35 years old (average = 19.59, SD = 3.75) of the city of Lima participated in the study. The results show that women are more likely to experience some degree of happiness; while people of the older age group have higher happiness scores than the younger age group. The results contribute to a better understanding of happiness and its relation to sociodemographic variables related to health and well-being. This provides important empirical information for the implementation of actions to promote the development of positive variables